Determinants of cash holdings of Chinese listed companies - zhao, yujie (2017)
"Cash is the king" has always been regarded as the central idea of corporate money management, which indicates that cash holding has an important effect on the companies. Many companies will hold different amount of cash. However, holding too much cash will also have negative impact on the companies. For example, opportunity costs and management costs will increase. The aim of this paper is to analyze the determinants of cash holding . The results have shown that the financial and governance characteristics have a significant impact on cash holdings. The results have shown that the financial characteristics have a significant impact on cash holdings. Debt structure, cash dividend and cash flow are significantly positively correlated with cash holdings; company size, leverage, bank debt and cash substitute are negatively correlated with cash holdings. In terms of the impact of governance factors on cash holdings, it is believed that the share proportion of senior managers ,legal person(lshare), and board size (bsize) are significantly positively correlated with cash holdings. Independent directors are positively related to cash holdings. Outstanding shares is significantly negatively correlated with cash holdings. The share proportion of the largest shareholder (fshare) and state are negatively correlated with cash holdings.